ANALISIS LIGHTING ARRESTER UNTUK MENGAMANKAN BUSBAR 150 kV TERHADAP GANGGUAN SURJA PADA GIS PECATU - Agus Kumara Putra, I Putu; Dyana Arjana, I Gede; Indra Partha, Cok. Gede (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUM, 2022)
GIS (Gas Insulated Switchgear) Pecatu is one of the GI built by PT. PLN (Persero) to provide energy continuity to its customers. In the GIS Pecatu there is no lighting arrester (LA) because the equipment in the GIS Pecatu is located indoors. Where there is only LA from the direction of the GI Nusa Dua to the GIS Pecatu with a distance of 12.08 km, so it is necessary to do study to find out whether the LA from the GI Nusa Dua direction to the GIS Pecatu can protect the busbar from the traveling wave of lightning surge . The results of the analysis showed using the software simulation method that LA from the direction of the GI Nusa Dua to the GIS Pecatu has been able to protect the GIS Pecatu busbar. Simulation results obtained that the current passing through the 150 kV busbar of 1,219 kA and the voltage on the busbar during a lightning surge of 4 kV. The voltage on the busbar and the current through the busbar during a surge is still within the tolerance of the maximum system voltage of 170 kV and the current ratio of 4 kA.